(untitled) (Metro Manila, Philippines, 2009)
Contents: The setting - Louang Namtha and bokeo in Historical and anthropological perspctive; Practices and propensities with respect to trafficking; Road construction problems; Temptations of material goods...
Keywords: Human trafficking,Buôn bán người